2006
DOI: 10.1007/s00417-005-0200-7
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 gene polymorphisms influence clinical features of open-angle glaucoma

Abstract: PON1 gene polymorphisms may influence the features of Japanese patients with OAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Mumcu et al reported that glaucoma patients had lower PON1 activity compared to controls and that the level of malondialdehyde (MDA), a marker of lipid peroxidation, showed a significant negative correlation with PON1 activity [ 45 ]. Other studies have shown that specific polymorphisms in the PON gene are associated with glaucoma risk [ 46 ]. Our study supports these findings by demonstrating a significant causal relationship between PACG and lower levels of GPX and reduced levels of PON activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mumcu et al reported that glaucoma patients had lower PON1 activity compared to controls and that the level of malondialdehyde (MDA), a marker of lipid peroxidation, showed a significant negative correlation with PON1 activity [ 45 ]. Other studies have shown that specific polymorphisms in the PON gene are associated with glaucoma risk [ 46 ]. Our study supports these findings by demonstrating a significant causal relationship between PACG and lower levels of GPX and reduced levels of PON activity.…”
Section: Discussionmentioning
confidence: 99%
“…The first two performed genotype analysis in Asian populations, one of which identified significantly higher R192 frequency in POAG patients compared to healthy controls [31]. The other, in contrast, has failed to find any statistically meaningful allelic distribution of the Q192R polymorphism between POAG, NTG or control groups [32]. Interestingly, the same study has established a positive regression between IOP levels and carrying the R192 allele (one or two copies) for both glaucoma patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis, which was performed on Caucasian subjects like the study last referred to, has not identified any statistically significant variation within PON1 phenotypes of PEXG, NTG and control groups, although a slight increase in QQ phenotype was present in NTG patients. One should note that the distribution of PON1 alleles, as well as IOP levels of glaucomatous eyes varies greatly between Asian and Caucasian populations, further complicating any conclusions to be drawn [32]. More research is needed to elucidate the role of PON1 function regarding glaucoma.…”
Section: Discussionmentioning
confidence: 99%